2016
DOI: 10.1016/j.aquaculture.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Soybean meal induces enteritis in turbot Scophthalmus maximus at high supplementation levels

Abstract: The goal of the present study was to find whether higher soybean meal (SBM) levels might trigger soybean meal-induced enteritis (SBMIE) in turbot. If so, caution must be taken when mixing ingredients containing saponins and other antinutrients to avoid SBMIE like symptoms. In a 8 week feeding trial conduced on turbot, three isonitrogenous and isolipidic diets were formulated to include 26%, 40% and 54% SBM to progressively replace 30%, 45% and 60% fish meal (FM) in a FM based diet, respectively. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
83
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 47 publications
19
83
5
2
Order By: Relevance
“…Surprisingly, the DFI remained at a similar level in both the FM ctrl and the SBM supplemented treatments. This is in contrast to previous studies which reported a DFI decrease when plant feedstuff was used at comparable substitution levels (Bai et al, ; Bonaldo et al, ; Fuchs et al, ; Gu et al, ). However, there are also investigations that detected no significant decrease in DFI (Sevgili et al, ; Yun et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, the DFI remained at a similar level in both the FM ctrl and the SBM supplemented treatments. This is in contrast to previous studies which reported a DFI decrease when plant feedstuff was used at comparable substitution levels (Bai et al, ; Bonaldo et al, ; Fuchs et al, ; Gu et al, ). However, there are also investigations that detected no significant decrease in DFI (Sevgili et al, ; Yun et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Solely in the SBM + degrad treatment a significant CF increase in comparison to the FM diet was detected. Conversely, Bonaldo et al () and Gu et al () found a significant decrease of the CF with increasing SBM inclusion. Here, Bonaldo et al () assumed that the lower CF was a consequence of a reduced muscle development, resulting in a lower thickness of turbot filets.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations